PENGARUH TRUST, COMMITMENT, COMMUNICATION DAN CONFLICT HANDLING TERHADAP LOYALITAS NASABAH PADA BNI SYARIAH KOTA BENGKULU - Kiki Pratama; Sri Ekowati ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2021)
This study aims to determine trust, commitment, communication and conflict handling, towards customer loyalty at BNI Syariah Kota Bengkulu. The sample in this study were 95 customers who saved at BNI Syariah Kota Bengkulu. Sampling using a questionnaire is done by incidental sampling. The analysis technique used is multiple linear regression, coefficient of determination and hypothesis testing. The results showed that from the calculation of the multiple linear regression equation, it can be seen that the direction of regression has a positive value with the equation Y = 2.466 + 0.192X1 + 0.221 X2 + 0.212X3 + 0.287 X4. The coefficient of determination is 0.577. This means that trust (X1), commitment (X2), communication (X3) and conflict handling (X4), affect loyalty (Y) by 57.7%, while the remaining 42.3% is influenced by other variables which are not researched in this study. The simultaneous hypothesis test results show a significance value of 0.000 smaller than 0.05, meaning that together trust (X1), commitment (X2), communication (X3) and conflict handling (X4) have a positive effect on loyalty (Y) . The partial hypothesis test results show that trust has a positive effect on loyalty with a significance value of 0.017 <0.05, commitment has a positive effect on loyalty, a significance value of 0.006 <0.05, communication has a positive effect on loyalty with a significance value of 0.017 <0 , 05, conflict handling has a positive effect on loyalty with a significance value of 0.005 <0.05.Keywords: Trust, Commitment, Communication, Conflict Handling, Customer Loyalty